TEORI INVISIBLE HAND ADAM SMITH DALAM PERSPEKTIF EKONOMI ISLAM - KAH, Rustam Dahar (Economica: Jurnal Ekonomi Islam, 2012)
Adam Smith as the founder of modern economics laid the basic foundation for economic development through the capitalist system in which capital factor used as a measuring tool for economic success. One opinion of Adam Smith "the theory of invivisble hand" in economic activity every individual has the full authority of his property and free use of economic resources in ways that he likes, disregarding the interests of the general public. This shows that capitalism has the right to have a peribadi an unlimited of the means of production, which is the driving force personal profit. Islam is essentially bringing the teachings to human life that comes the Koran and Hadith. Economic activity in the view of Islam is the guidance of life, in addition it is also a suggestion that has a dimension of worship. Wealth (material wealth) is trustworthy, thus the mandate that God bestowed it must be used together, not to suck other people or enslave other people. Islam allows every person to own property in person, but as it also enjoins on his property was to be used collectively (together), alms or spend a portion of such property in Allah. Economic activity in the view of Islam is not only material but more than that - "material plus" -. Islam has always stressed that every person living in a lawful manner. Islam also does not prohibit untukmelakukan economic activity, but Islam provides guidance and guidance in the form of Islamic values.Â